2014
DOI: 10.1016/j.taap.2014.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of cancer cell mitochondria- and NQO1-mediated redox activation of beta-lapachone, a potentially novel anticancer agent

Abstract: quinone oxidoreductase 1 (NQO1) accounted for its killing of cancer cells. However, the exact mechanisms of this effect remain largely unknown. Using chemiluminescence and electron paramagnetic resonance (EPR) spin-trapping techniques, this study for the first time demonstrated the real-time formation of ROS in the redox activation of beta-lapachone from cancer cells mediated by mitochondria and NQO1 in melanoma B16-F10 and hepatocellular carcinoma HepG2 cancer cells. ES936, a highly selective NQO1 inhibitor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…It is the main non-mitochondrial enzyme responsible for the reduction of CoQ10 in cells. Thus, NQO1 may “boost” mitochondrial metabolism by providing increased reduced CoQ10 species to facilitate oxidative mitochondrial metabolism [25, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…It is the main non-mitochondrial enzyme responsible for the reduction of CoQ10 in cells. Thus, NQO1 may “boost” mitochondrial metabolism by providing increased reduced CoQ10 species to facilitate oxidative mitochondrial metabolism [25, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies are currently underway in our laboratories to apply this novel method to investigate the redox mechanisms of cancer cell metastasis and the therapeutic effects of novel anticancer drugs, including the redox active beta-lapachone and other natural quinones that generate reactive oxygen species (ROS). In this context, our previous studies showed beta-lapachone as a potent killer of B16-F10 melanoma cells via the mitochondrial electron transport chain-mediated redox activation to form tumoricidal ROS [10]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, β-lapachone exhibited an anti-cancer effect in various types of cancer, including liver, breast, prostate, and colon cancer [1619]. In particular, it induced cytotoxicity in melanoma cells through reactive oxygen species, and NAD(P)H:quinone acceptor oxidoreductase (NQO) 1-mediated redox activation [20]. However, the anti-metastatic effects of β-lapachone on melanoma cells were rarely reported.…”
Section: Introductionmentioning
confidence: 99%